2022
DOI: 10.24251/hicss.2022.185
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Decision Assistance Versus Automated Decision-Making: Enhancing Knowledge Workers Through Explainable Artificial Intelligence

Abstract: While recent advances in AI-based automated decision-making have shown many benefits for businesses and society, they also come at a cost. It has for long been known that a high level of automation of decisions can lead to various drawbacks, such as automation bias and deskilling. In particular, the deskilling of knowledge workers is a major issue, as they are the same people who should also train, challenge and evolve AI. To address this issue, we conceptualize a new class of DSS, namely Intelligent Decision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…In order to complement the AI system, the human would have to adhere to its recommendations if and only if these recommendations are correct and override them otherwise. Empirical studies have shown, however, that humans are often not able to achieve this type of appropriate reliance 2 [1,4,5,6]. Instead, we often observe that humans either over-or under-rely on AI recommendations, or simply cannot calibrate their reliance.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…In order to complement the AI system, the human would have to adhere to its recommendations if and only if these recommendations are correct and override them otherwise. Empirical studies have shown, however, that humans are often not able to achieve this type of appropriate reliance 2 [1,4,5,6]. Instead, we often observe that humans either over-or under-rely on AI recommendations, or simply cannot calibrate their reliance.…”
Section: Introductionmentioning
confidence: 94%
“…In the general case, we may think of under-reliance as a behavior where A < Acc AI , and overreliance as A > Acc AI . Note that there exists other work that has been thinking of these terms with respect to behavior at the level of individual decisions [4,13].…”
Section: Correct Adherence Wrong Overridementioning
confidence: 99%
See 2 more Smart Citations
“…A core aspect is the identification of appropriate prompts to generate reasonable questions. This is similar to the problem of generating reasonable explanations in XAI 29 and often involves counterfactual reasoning. Counterfactuals feature prominently in human reasoning and communication about decisions.…”
Section: Reflection Machinementioning
confidence: 99%